Realism and Idealism in International Politics - Martin Griffiths (Routledge; 1st Edition, 1992)
â€œRealismâ€ and â€œidealismâ€ are both terms which have been used in differing, sometimes opposite, senses in the history of philosophy. They must therefore be employed with great caution. Dr. John H. Herz, in his recent study of the application of these terms to politics, seeks to define the sense in which he uses them. He writes in his preface that the book was in the main finished when the last war was ended and that little which had happened since required modification of his conclusions. To the reviewer it seems that further thought on the concepts employed in a perspective more removed from the disturbing influences of the war period would have been desirable.